Deep learning-empowered crop breeding: intelligent, efficient and promising - Wang, Xiaoding; Zeng, Haitao; Lin, Limei; Huang, Yanze; Lin, Hui; Que, Youxiong (Frontiers in Plant Science, 2023)
Crop breeding is one of the main approaches to increase crop yield and improve crop quality.However, the breeding process faces challenges such as complex data, difficulties in data acquisition, and low prediction accuracy, resulting in low breeding efficiency and long cycle.Deep learning-based crop breeding is a strategy that applies deep learning techniques to improve and optimize the breeding process, leading to accelerated crop improvement, enhanced breeding efficiency, and the development of higher-yielding, more adaptive, and diseaseresistant varieties for agricultural production. This perspective briefly discusses the mechanisms, key applications, and impact of deep learning in crop breeding. We also highlight the current challenges associated with this topic and provide insights into its future application prospects.